Peran Keterampilan Individual Dalam Dinamika Tim Futsal Di Smas Pesantren IMMIM - D, Muhammad Nur Ikram; Syarif, Muh Erfan; Martono, Martono (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aims to analyze the role of individual skills in the dynamics of the futsal team at SMAS Pesantren IMMIM. Futsal, as a team sport, requires a balance between individual abilities and solid teamwork. The research method uses a quantitative approach with a descriptive correlational survey design. The research population consists of all students enrolled in the futsal team at SMAS Pesantren IMMIM, totaling 24 individuals, with a sample selected using total sampling technique. The research instruments include a futsal individual skill test and a validated team dynamics questionnaire. The results of the study indicate a significant positive correlation between individual skills and futsal team dynamics (r = 0.742, p < 0.01). Dribbling skills contribute the most to team dynamics (38.2%), followed by passing accuracy (32.7%) and shooting precision (29.1%). These findings indicate that improving individual skills can strengthen team cohesion, communication, and collective performance. This study has practical implications for the development of futsal training programs that integrate the improvement of individual skills with the formation of positive team dynamics.